Pilihan Akad Pembiayaan Syariah untuk Pemberdayaan Pelaku Usaha Ternak Skala Mikro Berdasar Teori Economic Analysis of Law - Siti Hamidah; Siti Azizah (Journal of Agriprecision & Social Impact, 2024)
Article 8 of Act Number 20 years 2008 affirmed the government's commitment to Micro and Small Medium Enterprises to funding accurately and help obtain financing and services or other financial products, both conventional and Syariah systems. Contracts play an important role in economic activity or business. Function contracts give legal certainty, rules of the game, and tools evidence. Syariah funding contracts have many kinds which can be applied for various needs. Contract law is an open system, but the type of contract must be chosen to efficiently secure the distribution of funds. The role of the state needed to be precise following the purpose, for example, they do not finance properly the empowerment of micro-businesses in the livestock field. One theory that could help in legal problems in determining excellent choices is the economic analysis of law. This theory over law problems choice does not this can be resolved, as of theories it has the central idea to efficiency, among others the rule of law through contract.